DESAIN PEMBELAJARAN BERBASIS ICT UNTUK PENGEMBANGAN DESAIN PEMBELAJARAN BERBASIS METAKOGNISI (METACOGNITIVE LEARNING DESIGN) - Idzar Laela Istiqomah; Asyhar Lailatul Rahma; Nida Wahyu Sa’bani; Riris Eka Setiani (STKIP Subang, 2026)
The development of Information and Communication Technology (ICT) has brought significant transformation to the learning paradigm in modern education, particularly in supporting the creation of 21st-century learning that emphasizes critical, creative, collaborative, and independent thinking skills. The integration of ICT in the learning process is no longer seen merely as a medium for conveying information, but also as a strategic tool in building an interactive, flexible, and student-oriented learning environment (student-centered learning). One learning approach that is relevant to these demands is metacognition-based learning, namely the ability of students to be aware of, understand, control, and evaluate the thinking processes and learning strategies used during learning activities. This study aims to examine the implementation of ICT-based learning design in the development of metacognition-based learning. The study uses a qualitative approach with a type of library research through analysis of various scientific sources, such as academic journals, books, research articles, and relevant literature related to ICT, learning design, and metacognition. The results of the study indicate that ICT integration can support the development of students' metacognitive abilities through the stages of planning, monitoring, and evaluation in a more systematic and independent manner. The use of Learning Management Systems (LMS), e-learning, e-LKPD (learning materials), interactive multimedia, instructional videos, and digital learning applications has been proven to increase learning motivation, higher order thinking skills (HOTS), self-regulated learning, and students' reflective abilities. Furthermore, ICT-based learning designs and metacognition also encourage collaborative, constructivist, and problem-solving-oriented learning processes. Therefore, developing ICT based learning designs integrated with metacognitive approaches is a relevant and strategic learning innovation for improving the quality of learning processes and outcomes in the digital era.